Reading Bernstein, researching Bernstein - Davies, Brian, 1938-; Muller, Johan; Morais, Ana, 1939- (RoutledgeFalmer, 2004)
Basil Bernstein's work focused on the way that knowledge is produced, transmitted and learned. He is arguably one of the most important educational theorists of the late 20th century. This book, written by a team of international contributors, shows.